2007
DOI: 10.1021/je700188w
|View full text |Cite
|
Sign up to set email alerts
|

Densities and Excess Volumes of the 1,3-Dimethylimidazolium Methylsulfate + Methanol System at Temperatures from (313.15 to 333.15) K and Pressures from (0.1 to 25) MPa

Abstract: Densities of pure 1,3-dimethylimidazolium methylsulfate ionic liquid [MMIM][CH3SO4] and its mixtures with methanol have been measured with an accuracy of ±0.2 kg·m-3 over a temperature range from (313.15 to 333.15) K and a pressure range from (0.1 to 25) MPa using a vibrating tube densimeter. The isothermal compressibilities, isobaric expansivities, and excess volumes have been calculated. The uncertainties of these properties have been estimated to be ±0.05 GPa-1, ±0.2·10-4 K-1, and ±0.1 cm3·mol-1. The except… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
49
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 32 publications
7
49
2
Order By: Relevance
“…In this case, the TM EOS is almost as accurate as the ISM EOS and works better than the PR EOS. Table 9 include the deviations of the densities of the [Bmim][MeSO 4 ]system from the literature values [54,[61][62][63]. Also, Table 10 presents the average absolute deviation of the calculated densities of [C 4 mim][dca] IL from TM, vdW-CS-β, and PR compared with those obtained from experiment [24,[64][65][66].…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the TM EOS is almost as accurate as the ISM EOS and works better than the PR EOS. Table 9 include the deviations of the densities of the [Bmim][MeSO 4 ]system from the literature values [54,[61][62][63]. Also, Table 10 presents the average absolute deviation of the calculated densities of [C 4 mim][dca] IL from TM, vdW-CS-β, and PR compared with those obtained from experiment [24,[64][65][66].…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that densities of the pure ionic liquids are less dependent on pressure and temperature than typical organic liquids and therefore the observed isobaric expansivity and isothermal compressibility are considerably lower than usual [1][2][3][4][5][6][7][8][9][10][11][12]. Recently, we have noted that the excess volumes for the binary system (1,3-dimethylimidazolium methylsulfate ionic liquid + methanol) are exceptionally strongly influenced by temperature and pressure, and excess isobaric expansivity and excess isothermal compressibility have very high absolute values [1]. The same properties pertaining to the binary system (1-ethyl-3-methylimidazolium ethylsulfate + methanol) have been studied in this work.…”
Section: Introductionmentioning
confidence: 95%
“…This paper is a continuation of a systematic study on the volumetric properties of ionic liquids and ionic liquids mixed with organic liquids [1]. It has been inspired by the considerable interest in the unique properties of the ionic liquids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presented models require input data for their use that are critical properties, molecular weight and acentric factor that are available in the literature [1,13] and also in Table 1. Furthermore, in order to evaluate the degree of reliability of the presented models, they are also compared with AK, GC equation and experimental data [14][15][16][17][18][19][20][21][22][23][24][25][26]. Table 3.…”
Section: Resultsmentioning
confidence: 99%